Design and Analysis of Two-Port Self-Decoupled Highly Efficient MIMO Antenna for 5G New Radio Mid-Band (n1/n2/n3) Wireless Communication - Durai Pandurangan; Naveen Mishra (IEEE Access)
In this communication, dual port, self-decoupled, highly efficient multiple-input- multiple-output (MIMO) antenna for 5G new radio mid-band wireless communication is reported. The proposed MIMO antenna have a total foot print area of $0.82λ _{0}$ mm $_{x}~0.41λ _{0}$ mm x $0.0057λ _{0}$ mm, where $λ _{0}$ is free space wavelength considering 2.05GHz frequency. In this antenna configuration, single antenna unit is made up of optimized L-shape rectangular patch and ground loaded with defective ground structure (DGS) slot, printed on Rogers 5880 double-sided copper coated substrate with relative permittivity of 2.2. Antenna design is validated using characteristic mode analysis. To achieve antenna diversity, single unit is replicated and converted into two-port MIMO. Further, to show the effectiveness of antenna orientation on inter- element isolation two ports are placed in 0°, 90° and 180° orientation. The proposed structure provides 98.8% average radiation efficiency along with 4.1dBi peak gain in the direction of broadside radiation over the operating frequency. Mutual coupling between the antenna elements is discussed using surface current distribution and surface wave propagation. The maximum isolation is -41.9dB between ports, <0.008 envelope coefficient correlation, 9.99dB diversity gain, <0.4bits/s/Hz channel capacity loss, less than -1dB multiplexing efficiency, -31.2dB TARC and zero mean effective gain (MEG1/MEG2) ratio are some of the salient features of the proposed design. In order to verify the simulated results, the prototype is fabricated and the measurements are carried out using vector network analyzer and anechoic chamber. Good coherence between experimental and simulation results were found.